Bisphosphonate-Related Osteonecrosis of the Jaw Bones in a Patient with Ankylosing Spondylitis Receiving Anti-Tumor Necrosis Factor Treatment - Banu İŞLETEN,; Simin HEPGÜLER,; Selen BAYRAKTAROĞLU,; Gökhan KESER3, (Archives of Rheumatology, 2011)
Bisphosphonate-related osteonecrosis of the jaw bones is a rare, but well-recognized pathology, occurring mainly in patients receiving parenteral and high doses of bisphosphonates for the treatment of skeletal metastasis and/or hypercalcemia associated with cancer. However, to a lesser extent, this complication may also occur in patients receiving oral bisphosphonates for the treatment of osteoporosis. In this article, we present a 58-yearold female patient with ankylosing spondylitis (AS) who developed mandible osteonecrosis following long-term oral alendronate treatment for osteoporosis. Dental tooth extraction possibly triggered the occurrence of mandible osteonecrosis in this patient. This patient is notable for receiving concomitant anti-tumor necrosis factor (anti-TNF) treatment. To our knowledge, occurrence of bisphosphonate-related jaw osteonecrosis in a patient with AS receiving concomitant anti-TNF treatment has not been reported previously in the literature.